The Role of Small and Medium Enterprisesin Economic Development in Palestine - Hamdan, Badr (Finance and Business Economies Review, 2019)
The study aimed to measure the impact of small and medium enterprises on the economic development in Palestine.Through multiple regression models, to illustrate the relationship between the dependent variable (GDP at constant prices) and the independent variables (number of workers in small and medium enterprises, Small and Medium Enterprises, Value Added for SMEs and Investment in Palestine) during the period 1995-2017, using the ordinary least square OLS method. The study founda number of results, including a strong positive relationship between the independent variables and the dependent variable, and the coefficient of regression of the number of small and medium enterprises (0.053). Based on the study results, the study recommended providing financing facilities and low interest rates for small and medium enterprises by banking institutions. Therefore, those small and medium enterprises in Palestine can continue production.